Boncuklu Höyük: The earliest ceramics on the Anatolian plateau. (December 2017) - Spataro, M.; Fletcher, A.; Cartwright, C.R.; Baird, D.
Abstract: In this article 12 fired clay samples and an unfired marl sample from the late 9th and early 8th millennium cal BC site of Boncuklu Höyük (8300–7800 cal BC) in the Konya Plain, Turkey, were analysed by optical microscopy and SEM-EDX. The plant remains in the pottery fabrics were also examined in the variable pressure scanning electron microscope. Chemical analyses show that the same clays were used for multiple purposes, and more than one type of raw material was used to make the fired clay objects examined. Only one sherd showed signs of having added temper. The presence of scattered organic remains in the fabrics also suggests that the clay was minimally processed. Although the minerals present do not show any optical alteration, the shrinkage of the plant matter and the discolouring of bone inclusions suggested that all but one sample were fired, albeit at a relatively low temperature. These sherds are therefore regarded as among the earliest ceramic vessels known in southwest Asia, although the manufacturing technique was different to that used to make the contemporaneous PPNB ceramics found at Kfar HaHoresh in Israel. Highlights: Mineralogical and chemical analyses of the earliest ceramics in Anatolia SEM-EDX analyses show that the same clays were used for multiple purposes. Multiple clays used to make ceramics and almost no temper use Lack of parallels with ceramics from contemporary Kfar HaHoresh, Israel